An evaluation of efficacy of Lichtenstein mesh hernioplasty in emergency settings: a study in tertiary care hospital in Odisha - Panda, Srikanta; Mohapatra, Minati; Panigrahi, Sudhir Kumar; Sarangi, Anshuman; Jena, Somanatha (International Journal of Research in Medical Sciences, 2018)
Background: Despite the high incidence, the technical aspects of hernia repair continue to evolve making it the most common operations performed by general surgeons. Lichtenstein mesh hernioplasty repairs all hernias without distortion of the normal anatomy and with no suture line tension. This study was performed to evaluate the outcomes of Lichtenstein mesh herinioplasty in emergency inguinal hernia patients. Methods: A 84 patients were operated for complicated (obstructed irreducible) inguinal hernia. A follow-up period of 6 months using the Quantitative and Qualitative Measurement Instrument for evaluation of Lichtenstein hernioplasty outcomes was completed for 44 emergency patients. Results: The age incidence of the hernia patients in the study group was 40% (25-35 years) followed by 24% (15-25 years). The anatomical position of the hernia in the study group was to the right having a dominant percentage of 72% followed by left (24%) with none in bilateral. Early postoperative complications in mesh repair (Lichtenstein hernioplasty) comprising of factors like wound infection (10%), hematoma (5%), seroma (10%) was significantly lower compared to tissue repair with wound infection (20%), hematoma (5%) and seroma (25%). Further mesh rejection in Lichtenstein hernioplasty was 0% for the study population. Similarly, late postoperative complications in Lichtenstein hernioplasty comprising of factors like wound dehiscence (4%), neuralgia (27%) was significantly lower compared to tissue repair with wound dehiscence (27%), neuralgia (41%). Conclusions: The study revealed that the use of polypropylene prosthesis in the emergency setting (obstructed hernia) is safe and outcomes are satisfactory.